Sistem Pakar Diagnosis Penggunaan Softlens dengan Metode Forward Chaining - rahmi putri kurnia (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2018)
Softlens is a medical device that is attached to the cornea to help vision as a substitute for glasses. Currently Softlens are used freely. But many users are not aware of the impact of using Softlens. So there are problems that are harmful to the eye. Meanwhile, to consult with eye experts requires a lot of time and money. This study aims to facilitate the consultation process so as to minimize the risk of eye problems that may occur. By using the forward chaining method, knowledge from experts or eye specialists in the form of disease names and symptoms will be processed to get the rule. Where rule will be used in diagnosing the use of Softlens. From the results of system testing that has been done with sample data as many as 10 patients, compared with the results of expert diagnosis obtained the value of system accuracy is 80%. This level of accuracy shows that an expert diagnosis system using Softlens can be used to assist doctors in providing a diagnosis based on symptoms and can provide early prevention for users who use this expert system